Identification of DNA Sequences Specific for Vibrio vulnificus Biotype 2 Strains by Suppression Subtractive Hybridization - Lee, Chung-Te (American Society for Microbiology, 2005)
Vibrio vulnificus can be divided into three biotypes, and only biotype 2, which is further divided into serovars, contains eel-virulent strains. We compared the genomic DNA of a biotype 2 serovar E isolate (tester) with the genomic DNAs of three biotype 1 strains by suppression subtractive hybridization and then tested the distribution of the tester-specific DNA sequences in a wide collection of bacterial strains. In this way we identified three plasmid-borne DNA sequences that were specific for biotype 2 strains irrespective of the serovar and three chromosomal DNA sequences that were specific for serovar E biotype 2 strains. These sequences have potential for use in the diagnosis of eel vibriosis caused by V. vulnificus and in the detection of biotype 2 serovar E strains.